Prédicteurs de réussite en lecture dans l’Étude longitudinale française depuis l’enfance (ELFE): - Écalle, Jean; Dujardin, Émilie; Labat, Hélène; Thierry, Xavier; Magnan, Annie (Enfance, 2022)
This longitudinal study examined data from 2,767 children, followed over two years, who were assessed for early literacy at 4 years (HabLit4a) and then for reading at 6 years (HabLec6a). HabLit4a was evaluated using three tasks, i.e., letter-name knowledge, phonological skills and vocabulary, and HabLec6a was assessed based on four tasks, namely phonemic segmentation, word reading, listening comprehension, and reading comprehension. The weights of three socio-demographic variables - parental education level (PEL), family income (FI) and parental literacy practices (ParLitPr)–and two individual variables–age and gender–were also examined. Results from a structural equation analysis show a strong link (.68) between HabLit4a and HabLec6a. All variables directly affect performance at 4 years and PEL has the highest weight (.25) for HabLit4a. The age effect on skills favours older children and this is more pronounced in girls. The ﬁve variables also have an indirect effect on HabLec6a via HabLit4a:.17 for PEL and age. In addition to the expected results, and in line with what has been observed in other languages, the current study also distinguishes between two socio-economic variables, namely NEP and RF: The results show the level of parental education has the greatest weight for reading level at the end of Grade 1.